2014
DOI: 10.1111/emip.12028
|View full text |Cite
|
Sign up to set email alerts
|

Automated Scoring of Constructed‐Response Science Items: Prospects and Obstacles

Abstract: Content-based automated scoring has been applied in a variety

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 33 publications
1
63
0
2
Order By: Relevance
“…Although science practices such as explanation and argumentation are carried out by means of language, extended text responses written by students are not frequently utilized to inform student learning in science classrooms (Kuo & Wu, ). Automated text scoring can make a real‐time assessment of extended text responses possible without the involvement of extensive time and effort (Liu et al, ; Sherin, ). Automated text scoring occurs when a text is assigned a score on a predetermined scale through various statistical and natural language processing (NLP) techniques.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Although science practices such as explanation and argumentation are carried out by means of language, extended text responses written by students are not frequently utilized to inform student learning in science classrooms (Kuo & Wu, ). Automated text scoring can make a real‐time assessment of extended text responses possible without the involvement of extensive time and effort (Liu et al, ; Sherin, ). Automated text scoring occurs when a text is assigned a score on a predetermined scale through various statistical and natural language processing (NLP) techniques.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The scales can be established dichotomously (0–1) or in multiple scoring levels such as 0–2 or 0–5. As originally developed in language assessment, automated text scoring can be used to assess the content of the writing piece (Liu et al, ; Nehm, Ha, & Mayfield, ) or the quality or structure of the overall writing (Bridgeman, Trapani, & Attali, ). The noted benefits of automated text scoring include a reduction in time and effort as well as an establishment of consistency by eliminating human bias.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The most recent evaluation of the c-rater approach ) took advantage of some refinements introduced by Sukkarieh and Bolge (2008). O. L. Liu et al (2014) concluded that c-rater cannot replace human scores, although it has shown promise for use in lowstakes settings.…”
Section: Automated Scoringmentioning
confidence: 99%
“…MCAD systems address part of a complex problem [Carberry and McKenna, 2014] and are complex software tools that require not only a thorough understanding of the various functionalities provided by the system, but also the application of efficient strategies to create high quality CAD models. Based on related research, this issue can be considered a particular type of the "content-based constructed responses" problem [Liu et al, 2014].…”
Section: Supplementary Backgroundmentioning
confidence: 99%
“…Computer Aided Design (CAD) systems are complex software tools whose learning requires correctly managing the functionality provided by the system while applying proper strategies to create high quality CAD models ("content-based constructed responses" [Liu et al, 2014]). CAD models are a relevant part of industrial product design, which is a complex process that requires evaluation [Bailey and Szabo, 2006] and [Waks et al, 2011].…”
Section: Introductionmentioning
confidence: 99%